Controlling alginate gel degradation utilizing partial oxidation and bimodal molecular weight distribution - Boontheekul, Tanyarut; Kong, Hyun-Joon; Mooney, David J. (Biomaterials, 2005)
Degradability is often a critical property of materials utilized in tissue engineering. Although alginate, a naturally derived polysaccharide, is an attractive material due to its biocompatibility and ability to form hydrogels, its slow and uncontrollable degradation can be an undesirable feature. In this study, we characterized gels formed using a combination of partial oxidation of polymer chains and a bimodal molecular weight distribution of polymer. Specifically, alginates were partially oxidized to a theoretical extent of 1% with sodium periodate, which created acetal groups susceptible to hydrolysis. The ratio of low MW to high MW alginates used to form gels was also varied, while maintaining the gel forming ability of the polymer. The rate of degradation was found to be controlled by both the oxidation and the ratio of high to low MW alginates, as monitored by the reduction of mechanical properties and corresponding number of crosslinks, dry weight loss, and molecular weight decrease. It was subsequently examined whether these modifications would lead to reduced biocompatibility by culturing C2C12 myoblast on these gels. Myoblasts adhered, proliferated, and differentiated on the modified gels at a comparable rate as those cultured on the unmodified gels. Altogether, this data indicates these hydrogels exhibit tunable degradation rates and provide a powerful material system for tissue engineering.